Masculinity, citizenship and political objection to compulsory military service in the South African Defence Force, 1978-1990 - Conway, Daniel John (Rhodes University, Faculty of Humanities, Department of History)
This thesis conceptualises compulsory military service and objection to it as public performative acts that generate gendered and political identity. Conscription was the primary performance of citizenship and masculinity for white men in apartheid South Africa. Conscription was also a key governance strategy both in terms of upholding the authority of the state and in engendering discipline in the white population. Objection to military service was therefore a destabilising and transgressive public act. Competing conceptualisations of masculinity and citizenship are inherent in pro and anti-conscription discourses. The refusal to undertake military service places men outside the accepted means of graduating to ' real' manhood and patriotic citizenship. Although objection can be an iconic and transgressive act, objectors have an essentially ambivalent subjectivity in the public realm. Objectors are 'strangers' in a socially constructed and gendered binary of 'insiders' and 'outsiders' . This ambivalent status creates opportunities but also constraints for the performance of objection. The thesis analyses the effectiveness of objectors' performances and argues that there is a distinction between a radical challenge to hegemonic conceptions of militarised masculinity and citizenship and assimilatory challenges. The tension between radicalism and assimilation comes to the fore in response to the state's attacks on objectors. The militarised apartheid state is defined as not only masculine but heteronormative terms and it is the deployment of sexuality that is its most effective means of stigmatising and restricting the performance of objection. The thesis uses interview material, archival data and case studies and concludes that objectors (and their supporters) weaved multiple narratives into their performances but that as the 1980s progressed, the performance of objection to conscription became assimilatory and this demonstrates the heteronormativity of the state, military service and the public realm.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Conscientious objectors -- South Africa; End Conscription Campaign (South Africa); National service -- South Africa; Draft -- South Africa; South Africa -- Military policy; Masculinity -- South Africa; South Africa. South African Defence Force; Gays in the military -- South Africa